Pengawasan Majelis Pengawas Daerah terhadap Notaris setelah berlakunya Undang-Undang No. 2 Tahun 2014 tentang Perubahan atas Undang-Undang No 30 Tahun 2004 tentang Jabatan Notaris - MUHAMMAD HARIS (Syariah: Jurnal Hukum dan Pemikiran, 2014)
The Notary is a public official who was appointed by the Minister. Notaries are authorized officer to make authentic act of the civil. With this relationship beetwen the notary and the community, it would require a Notary professional supervision. Supervision of the Notary conducted by the Regional Supervisory Council who was inaugurated by the Minister as specified in the Notary Act. After the enactment of The Law Number 2 Year 2014 about The Amendment to Law Number 30 Year 2014 concerning Notary, there are some changes in regulations about supervision and guidance that will be undertaken by the Regional Supervisory Council. This law says that supervision of the Notary conducted by the Regional Supervisory Council, while the development under the authority of the Regional Supervisory Council before is now a Notary Honorary Council authority.